Isolation and characterization of potential phosphate solubilizing bacteria in two regions of Senegal - Nadiéline, Christian Valentin; Ndiaye, Mame Farma; Fall, Saliou; Krasova, Tatiana; Le Quéré, Antoine; Diouf, Diégane (Academic Journals, 2019)
Many soils of the inter-tropical regions are P-deficient because of their high fixing power and low P content. Rock phosphate resources used to produce the phosphate fertilizers are exhausted and chemical fertilizer are causing environmental degradation. This issue raised the question of sustainability of fertilization and subsequently has enhanced the interest in the use of microorganismsas biofertilizers. The aim of this study is to isolate and characterize potential P solubilizing bacteria (PSB) from two P deficient agricultural regions in Senegal. Twelve potential PSB were selected and further screened for other plant growth promoting traits (Indole-3-acetic acid (auxin) and siderophore production) and characterized by 16S rDNA sequencing. All the isolates produced auxin and seven of them produced siderophore. DNA sequencing showed that five isolates were affiliated to the genus Bacillus, four to the genus Staphylococcus, two to the genus Microbacterium and one isolate showed high similarities with members of the genus Burkholderia. The selected bacteria will further be tested on some plants to assess their biofertilization potential.
Early studies proved the existence of a group of soil free living bacteria stimulating plant growth, which was called plant growth promoting rhizobacteria (PGPR) (Kloepper and Schroth, 1978).
Keywords: 16S rDNA; indole-3-acetic-acid (IAA); phosphate solubilizing bacteria (PSB); siderophore